Application and Equipment of Preparation Technology of Ferroelectric Thin Film Materials in Sports Industry. (24th August 2022) - Xu, Yali
Abstract : With the rapid development of the integrated circuit industry, ferroelectric thin film materials and technologies have become increasingly important. Ferroelectric materials have been widely used in aerospace, information storage, artificial intelligence, microelectromechanical, wearable devices, and other fields. Traditional sports is an important carrier of traditional culture. It contains the sports cultural resources created and precipitated by the Chinese nation for thousands of years, and all sectors of society are also paying great attention to this. Under the background of the market economy system and the major premise of the vigorous development of the cultural industry and sports industry, industrialization is obviously the inevitable choice for traditional sports to break through the difficulties and seek development, and it will also promote the further inheritance and promotion of traditional sports. The complex combination causes its performance to decrease or even fail. Therefore, it cannot cause foresee losses and disasters. It has important application value and significance to master the performance changes and mechanisms of ferrous film materials under different adding environments. This paper takes ferroelectric Pb (Zr0.52 Ti0.48 )O3 (PZT)Bi3.15 Nd0.85 Ti3 O12 (BNT) as the research object, proposes the preparation of sol coating for thin film materials, and studies the preparation parameters PZT of the sol electric ferroelectric method. Electrical method and BNT electrical film properties affect iron and physical experiments on the properties of iron. The influence of the best sol-iron coating method on the electrical properties of PZT and BNT films is the ferroelectric properties of the 700°C layer of high-temperature gas, 10-layer PZT films, and 8-layer BNT films. The elasticity and elastic moduli of PZT and BNT films are 66.8 MPa and 99.6 MPa and 159.3 GPa and 189GPa, respectively; the elastic coefficients of PZT and BNT films are15.4 × 10 10 N/m 2 and18.4 × 10 10 N/m 2, and their elastic coefficientse 31 decrease with accompanying increase in swallowing. And with the disease of reading and writing field strength, as the speed becomes faster and slower, the carriers have more time to move to the brain wall, so the intensity is also intuitive. It has strong practicability and feasibility to popularize the material and manufacture the equipment of the current sports equipment club.